Essentials of construction planning and scheduling - Robertson, Graham (ICE Publishing, 2021)
Essentials of Construction Planning and Scheduling is a practical handbook on the planning of construction projects, from tender through to project completion. The book provides essential tools to plan a project and communicate that plan to the whole project team to enable all team members to see what should be happening at every stage of a project.